(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Khalitya and Palitya are two disorders described in Ayurveda texts which are similar to hair loss. According to concept of Tridosha, it may be produced due to Prakopa or Vridhi of Vata and Pitta Dosha. In Ayurvedic terms, hair fall is coined out as ‘Keshpatana’. The production of first Dhatu (Rasa Dhatu) in qualitative form is responsible for the production of next (Uttarouttar) Dhatu and upto Sukra Dhatu. The nutrients required for Asthi Dhatu are responsible for the quality and strength of hair. Aim and objective: Evaluation of the combined effect of Anutaila Nasya and Keshamitra yoga in Keshpatana in comparison of only Keshamitra yoga, to evaluate the efficacy of Nasya Karma in management of Keshpatana. Material and methods: In the present clinical study, 60 patients of Keshpatana were selected randomly from the O.P.D & I.P.D of Gurukul Campus, U.A.U, Haridwar and were randomly divided into two groups (30 patients in each). Out of which 6 patients went to LAMA. Keshpatana in Group A were treated with Anutaila Nasya, which was given in schedule for 3 courses of 7 days and with a gap of 3 days and Keshamitra Yoga. Group B was given Keshamitra Yoga 5gm BD orally for 30 days. Result: The therapeutic effect of the treatment was assessed on both sign and symptoms and tests. Group A marked relief (≥75-99% relief) in 12 patients (46.15%), moderate relief (≥51-74% relief) was seen in 13 patients (50%) and 1 patient (3.8%) showed mild relief. In group B, 19 patients (73.07%) showed mild relief, 6 patients (23.07%) showed moderate relief, and marked relief (≥ 75-99% relief) was seen in 1 patient (3.8%). Conclusion: Anutaila Nasya reveals encouraging results then Keshamitra Yoga by providing relief in Keshpatana and by reducing the hair fall significantly.